1985
DOI: 10.1111/j.1365-2125.1985.tb05094.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of buccal nitrate on left ventricular haemodynamics and volume at rest and during exercise‐induced angina.

Abstract: A novel approach has been employed to characterize the effects of a cardioactive drug on left ventricular haemodynamics and volume by simultaneously determining cardiac stroke volume (thermodilution) and left ventricular ejection fraction (nuclear probe). The effects of glyceryl trinitrate were evaluated in 12 patients with angiographically proven coronary artery disease at rest and 3, 7, 15 and 30 min following 10 mg buccal nitroglycerin (Suscard) administration. The impact of the drug on left ventricular hae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
3
3
0
Order By: Relevance
“…Using the method of Thadani et al [21] to provoke pacing-induced myocardial ischaemia in patients with chronic obstruc tive coronary artery disease, we [ 11 ] found early and sus tained improvements in left ventricular filling pressures, peak filling rate (diastolic filling), and ejection fraction after treatment with 5 mg buccal nitroglycerin. These results are consistent with those of Silke et al [ 12] who found similar improvements in left ventricular volume changes with buccal nitroglycerin, although higher doses ( 10 mg) were used.…”
Section: <00001supporting
confidence: 83%
See 1 more Smart Citation
“…Using the method of Thadani et al [21] to provoke pacing-induced myocardial ischaemia in patients with chronic obstruc tive coronary artery disease, we [ 11 ] found early and sus tained improvements in left ventricular filling pressures, peak filling rate (diastolic filling), and ejection fraction after treatment with 5 mg buccal nitroglycerin. These results are consistent with those of Silke et al [ 12] who found similar improvements in left ventricular volume changes with buccal nitroglycerin, although higher doses ( 10 mg) were used.…”
Section: <00001supporting
confidence: 83%
“…also appears to have doubtful efficacy in patients with stable angina; it is thus probably unsuitable for the man agement of unstable angina [10]. Buccal nitroglycerin has an unique delivery system which produces satisfac tory blood levels and haemodynamic effects within 1 min of administration [7,8,11,12], after which ade quate blood levels persist for up to 6 h [7,8,13], Theo retically it could be used during the acute phase of unsta ble angina and subsequently for long-term manage ment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the description of the haemodynamics of nicardipine, the left ventricular ejection fraction and volume were measured using a non-imaging scintillation probe (Nuclear Stethoscope-Bios Inc). As previously reported, this technique allows the left ventricular ejection fraction to be determined with a reproducibility of within <4% at rest and <5% during constant load supine bicycle exercise (Silke et al, 1985b). Over a similar dose range (1.25-10.0 mg), the haemodynamic dose-response effects described above were confirmed in 12 patients with similar demographic characteristics to the previous study.…”
Section: Intravenous Dose-response Studiessupporting
confidence: 80%
“…The doses and routes of drug administration were those which have been previously demonstrated to result in substantial pharmacodynamic effects (Silke et al, 1985a(Silke et al, , 1986; the route of drug administration was selected based on ease of administration and laboratory convenience. These considerations suggest that our data reliably describe the acute pharmacodynamic actions of celiprolol, nitrate and their combination in coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%